Support for Safer Opioid Prescribing Practices: A Catalog of Published Use After Orthopaedic Surgery. (15th November 2017) - Lovecchio, Francis; Derman, Peter; Stepan, Jeffrey; Iyer, Sravisht; Christ, Alexander; Grimaldi, Peter; Kumar, Kanupriya; Ranawat, Anil; Taylor, Samuel A.
Abstract : The opioid epidemic places enormous social, ethical, and legal pressure on orthopaedic prescribers to balance postoperative pain relief with responsible prescribing practices. A catalog of the type and average number of narcotic pills used by patients recovering from various orthopaedic surgeries may serve as a starting point for safe opioid prescribing strategies. Prescriber education and guidelines that depersonalize discussions about the maximum strength and number of pills that can be provided may reduce overprescribing. The large ranges of opioid consumption reported in many studies challenge the notion that opioid use is an objective measure of pain level and prompt further investigation into the variety of individual or cultural factors that may influence postoperative opioid consumption.